2018
DOI: 10.1101/481010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Repression of an activity-dependent autocrine insulin signal is required for sensory neuron development inC. elegans

Abstract: 24Nervous system development is instructed both by genetic programs and activity-dependent 25 refinement of gene expression and connectivity. How these mechanisms are integrated remains 26 poorly understood. Here, we report that the regulated release of insulin-like peptides (ILPs) 27 during development of the C. elegans nervous system accomplishes such an integration. We 28 find that the p38 MAP kinase PMK-3, which is required for the differentiation of chemosensory 29 BAG neurons, functions by limiting expre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Autocrine peptide signaling is ubiquitous in other brains as well 97,98 , suggesting it supports important aspects of neural function. For example, autocrine neuropeptide pathways are known to mediate cell-autonomous feedback [99][100][101][102][103][104] , and are therefore often suggested to maintain neuronal homeostasis; this may be particularly important to regulate the activity of tonically signaling neurons, such as the oxygen-sensing neurons. In the motor circuit, ostensibly autocrine signaling may play a further role by coordinating the activities of neighboring neurons with similar gene expression patterns.…”
Section: Neuropeptide Signaling Links Specific Components Of the Nerv...mentioning
confidence: 99%
“…Autocrine peptide signaling is ubiquitous in other brains as well 97,98 , suggesting it supports important aspects of neural function. For example, autocrine neuropeptide pathways are known to mediate cell-autonomous feedback [99][100][101][102][103][104] , and are therefore often suggested to maintain neuronal homeostasis; this may be particularly important to regulate the activity of tonically signaling neurons, such as the oxygen-sensing neurons. In the motor circuit, ostensibly autocrine signaling may play a further role by coordinating the activities of neighboring neurons with similar gene expression patterns.…”
Section: Neuropeptide Signaling Links Specific Components Of the Nerv...mentioning
confidence: 99%
“…The invertebrate neural circuits were initially thought to be genetically hardwired (Jin et al , 1999; Gally & Bessereau, 2003; Hiesinger et al , 2006; Klassen & Shen, 2007), although neural activity can regulate the remodeling or plasticity (Zhao & Nonet, 2000; Sachse et al , 2007; Tessier & Broadie, 2009; Thompson‐Peer et al , 2012; Hart & Hobert, 2018; Cuentas‐Condori et al , 2019). However, recent studies have shown that neuronal activity during embryogenesis regulates neuronal differentiation (Horowitz et al , 2019), presynaptic subcellular specificity (Wang et al , 2021) in C. elegans , indicating the important role of experience‐independent activity in circuit development. In vertebrates, it is well known that neural activity regulates synaptic formation and plasticity (Hooks & Chen, 2020; Pan & Monje, 2020).…”
Section: Discussionmentioning
confidence: 99%